The Influence of Live Streaming, Content Marketing, and Online Customer Reviews on Purchase Decisions (A Study on TikTok Shop Ceilo Official) - Gita Mardhatilla Noviarafita; Lia Nirawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Live Streaming, Content Marketing, and Online Customer Review on Purchasing Decisions in purchases via E-commerce on the TikTok Shop application. With a focus on ceilo official followers the method used in this study is associative with a quantitative approach. Data was collected through a questionnaire distributed to 98 respondents with a purposive sampling technique. The results of the study indicate that Live Streaming has a positive and significant effect on Purchasing Decisions. Content Marketing has a positive and significant effect on Purchasing Decisions. However, Online Customer Review does not have a significant effect partially on Purchasing Decisions. However, simultaneously, the three variables have a significant effect on Purchasing Decisions on Ceilo official TikTok Shop.